Green manufacturing of high-value extracts from milk thistle seeds: Parameters that affect the supercritical CO2 extraction process. (September 2022) - Milovanovic, Stoja; Lukic, Ivana; Kamiński, Piotr; Dębczak, Agnieszka; Klimkowska, Kamila; Tyśkiewicz, Katarzyna; Konkol, Marcin
Abstract: The aim of this study was to provide insights into parameters that affect the oil extraction from an industrially valuable raw material (milk thistle) using green solvent supercritical CO2 . The effect of plant origin, cultivation year, and seeds storage on extraction yield has been explored. Furthermore, the effects of high-pressure unit design and initial plant material amount have been examined. Pressure (200–450 bar) and temperature (40–80 °C) have been tested to improve the recovery of essential fatty acids and phenolic compounds. Moreover, solid residues after the material pretreatment and supercritical CO2 extraction served as the substrates for waste valorization. The characterization of obtained high-value extracts has been carried out by chromatographic (using gas chromatographs combined with mass spectrometer and flame ionization detection) and spectrophotometric assays (for total phenolic and flavonoid compounds as well as a radical scavenging ability). It was shown that the tested supercritical CO2 extraction process parameters determined extraction kinetics and allowed the extract separation from raw milk thistle seeds and waste material (3–32 mass %) rich in linoleic acid (up to 515 mg/g) and total phenolic compounds (up to 30 mg GAE/g). Graphical Abstract: ga1 Highlights: Milk thistle origin, cultivation year and seeds storage determined extraction kinetic. High-pressure unit design and amount of plant material used had an effect on the SFE process. Variation in pressure and temperature allowed separation of up to 32 g oil / 100 g seeds. Raw and waste seeds of milk thistle are valuable source of bioactive compounds. Oils are rich in the essential fatty acid (linoleic acid up to 515 mg/g extract).